A research, development and innovation management system for small and medium enterprises - Pereira, João (2018)
In an increasingly competitive market, innovation plays an extremely important role in organizations, since it enables them to produce goods or services that are more valuable to their customers than what their competitors have to offer. For this reason, many organizations develop processes that support innovation. In Portugal, the Portuguese Standard 4457:2007 (NP4457), which defines the requirements for a Research, Development and Innovation Management System (RDIMS), was introduced in 2007. These requirements act as guidelines for organizations that recognize the importance of innovation. The purpose of this paper is to present a RDIMS that supports the management of innovation in the company Gelado Colorido, based on NP4457. A case study was carried out in a business environment with a duration of 6 months. After analysing the reality of the company an Innovation Support System was presented divided in: Strategic Definition, Innovation Process and RDIMS Evaluation. Although it was created for a specific firm, it is based on generic references and it doesn’t involve specific activities or characteristics of the organization or industry for which it was intended, which makes it possible to adapt it to other SMEs that are interested in improving innovation management performance and/or in the NP4457 certification.